Introduction: Collective Memories of Colonial Violence - Licata, Laurent; Volpato, Chiara (International Journal of Conflict and Violence (IJCV), 2010)
Colonialism, that Loomba calls "the most complex and traumatic relationship in human history" (2005, 8), has left its mark on international relations, social relationships within nations, and the ideologies and imaginaries of virtually all the peoples of the world. Understanding colonialism and its consequences is therefore essential to comprehending the dynamics and conflicts of the contemporary world. This special focus was born out of a desire to bring social psychological studies on colonialism to broader attention.